Factors that affect non-muslim's preferences toward islamic banking / Nadiah Amirah Nor Hishamudin - Nor Hishamudin, Nadiah Amirah (2019)
Malaysia is one of the country that accept the concept of Islamic Banking and has been promoting the idea of implementing the system of Islamic Banking with the aim to expand the circle of Muslim unity and also to make sure a fair distribution and utilization of fund that comply with Islamic Principles in order to be parallel with the system in conventional bank. As for now, the existence of dual bank system, Malaysia has come out with numerous choices for customers to choose the products and services that can meet with their needs and wants. This research has come out with an important contribution towards Islamic Bank in order for them to understand the attitudes of the customers, their preferences, and characteristics. Besides that, this research also has the purpose to investigate if there are any demographic that influence awareness, understanding, and the perceptions towards Islamic Bank among Non-Muslim in Malaysia. There are a total of 60 respondents is drawn for this research from Malaysia. From the respondents, it shows more than half of the respondents are actually aware about the Islamic Bank in Malaysia. Pearson Correlation Coefficient analysis is being conducted, and the results show all the three independent variables have a positive relationship with the preferences of Non-Muslim toward Islamic Bank. The three independent variables are Sharia compliances, Knowledge of Non-Muslim customers, and also trust and confidence. This research provides theoretical and also managerial implications for Islamic Bankin order for the bank to attract Non-Muslim customers.